Epidemiological profile of urinary tract infection among pregnant women in Karbla, Iraq - Amer Hammadi; Ali Shakir; Aabdulridha Al-Asady; zaynab abd_alkarem; Shaymaa Ali; Hasan Alsailawi; Ammar Ghareeb; Mustafa Mudhafar; Qais Lahhob (Microbes and Infectious Diseases, 2025)
Objectives: The current study aims to determine the cause of urinary tract infection (UTI) during pregnancy and relation of age and pregnancy period with these infection.  Methods: Urine samples were collected from pregnant women suspected to UTI infection, in the Obstetrics and Gynecology Hospital and determine causal agent of UTI infection by microscopy, cultural character and biochemical tests. Results: The result showed UTI cause by bacterial infection of E .coli staphylococcus aureus, Klebsiella and Streptococcus in arrangement. There is relation between UTI and age of patient women most infection in medial age and there is relation also with pregnancy period most infection happened in third pregnancy trimester Conclusion: The current report will help determine the cause of UTI infection in pregnant women and which period of pregnancy happened and which age infected more.